The heirs of Archimedes : science and the art of war through the Age of Enlightenment - Steele, Brett D.; Dorland, Tamera (Dibner Institute studies in the history of science and technology., 2005)
Essays analyze the connections between science and technology and military power in the late medieval, Renaissance, and Enlightenment periods. The integration of scientific knowledge and military power began long before the Manhattan Project. In the third century BC, Archimedes was renowned for his research in mechanics and mathematics as well as for his design and coordination of defensive siegecraft for Syracuse during the Second Punic War. This collection of essays examines the emergence during the early modern era of mathematicians, chemists, and natural philosophers who, along with military engineers, navigators, and artillery officers, followed in the footsteps of Archimedes and synthesized scientific theory and military practice. It is the first collaborative scholarly assessment of these early military-scientific relationships, which have been long neglected by scholars both in the history of science and technology and in military history. From a historical perspective, this volume investigates the deep connections between two central manifestations of Western power, examining the military context of the Scientific Revolution and the scientific context of the Military Revolution. Unlike the classic narratives of the Scientific Revolution that focus on the theories of, and conflicts between, Aristotelian and Platonic worldviews, this volume highlights the emergence of the Archimedean ideal--in which a symbiosis exists between the supply of mechanistic science and the demand for military capability. From a security-studies perspective, this work presents an in-depth study of the central components of military power as well as their dynamic interactions in the political, acquisitional, operational, and tactical domains. The essays in this volume reveal the intellectual and cultural struggles to enhance the capabilities of these components--an exercise in transforming military power that remains relevant for today's armed forces. The volume sets the stage by examining the innovation of gunpowder weaponry in both the Christian and the Islamic states of the late medieval and Renaissance eras. It then explores such topics as the cultural resistance to scientific techniques and the relationship between early modern science and naval power--particularly the intersecting developments in mathematics and oceanic navigation. Other essays address the efforts of early practitioners and theorists of chemistry to increase the power and consistency of gunpowder. The final essays analyze the application of advanced scientific knowledge and Enlightenment ideals to the military engineering and artillery organizations of the eighteenth century. The volume concludes by noting the global spread of the Archimedean ideal during the nineteenth century as an essential means for resisting Western imperialism.